Relationship Between Speed Aand Agility to Dribble Results in Futsal Games - Edo Tri Andika; Syafaruddin Syafaruddin; Achmad Richard Victorian (Journal Physical Education, Health and Recreation, 2021)
This study aims to determine the relationship between speed and agility in the dribbling ability of students at the extracurricular activities of SMA Negeri 21 Palembang. This type of research is descriptive and uses a correlation design. The population of this research is the extracurricular students of SMA Negeri 21 Palembang totaling 40 students. The sample in this study was taken as a whole or a total sampling of 40 students. The instrument in this study was to test speed using a 40-meter run test, agility using a zig-zag run test, and dribbling using a dribbling or dribbling test. The data analysis technique is processed by percentages and hypothesis testing using computer-assisted correlation in the Excel and SPSS 22 programs. Based on the percentage analysis of the data obtained, namely for speed results, a percentage of 100% is received, totaling 40 students have an average speed result with an excellent category. Agility results obtained a ratio of 100%, totaling 40 students who have an average agility result with a good variety. And for the results of the dribbling ability, the percentage of 100% obtained is that 40 students have an average dribbling ability, resulting in a suitable category. The results of the correlation analysis technique were obtained, showing that the normality test of the variables X1, X2, and Y was obtained, which was normally distributed. The correlation value between X1 and Y=0.60, the value of X2 and Y=0.70, and the importance of X1, X2, and Y=0.65 showed a moderate level of correlation. The application of this research is that speed and agility have a relationship with the results of dribbling ability. Keywords: Speed, Agility, dan Kemampuan Dribble pada Futsal.